Determinants of intensity of adoption of old coffee stumping technology in Dale Wereda, SNNPRS, Ethiopia - Arega, M. (Haramaya University, 2009)
Coffee is the main cash and export crop in Southern Ethiopia as well as in the whole Ethiopia. The country’s export earnings from this crop exceeds all other agricultural products. Low production and productivity, which are mainly associated with poor adoption of improved technology, oldness of coffee trees and poor pruning and recycling system, especially stumping, were among the major problems. Adoption of improved technologies is one of the most promising ways to increase productivity and production in Ethiopia. However, the adoption and dissemination of these technologies is constrained by various factors. To this end, the aim of this study was to empirically examine factors affecting adoption and intensity of adoption of old coffee stumping technology in the study area. Fourstage sampling procedure was followed to select rural kebeles and households for the study. First, 59 coffee grower PAs were selected purposively from 79 PAs. Second, the 59 PAs were stratified based on their coffee production potential as specialized coffee PAs and diversified PAs, 42 and 17 PAs accordingly. Thirdly, proportional to size four PAs were selected, 3 from specialized and one from diversified. Finally 160 coffee grower household heads were selected randomly using probability proportional to size sampling. Structured interview schedule was developed, pre-tested and used for collecting the essential quantitative data for the study from the sampled households. Focus group discussion was used to generate qualitative data. In addition, secondary data were collected from relevant sources such as wereda office of Agriculture and others. The result of the study indicated that majority of farmers in the study area did not prefer stumping to solve problems of low productivity due to old age of coffee trees. Instead of stumping, they preferred to wait with this limited production, because they are feared that even may loss the whole production. Moreover, farmers’ practice was found largely to deviate from research and extension recommendation specially the management which is done after stumping. Results of the econometric model indicated that households perception about the problem of coffee oldness and decline of production, participation in extension events like field day visit and frequency of visit, education, types of social participation, having of old coffee which could be stumped, producing coffee seedlings (participation in other extension activity) and getting coffee plants from common holdings were important variables which had positively and significantly influenced adoption and intensity. The overall findings of the study underline the importance of institutional support in the area of extension especially creating awareness on the problem of coffee oldness and decline of production; and the research should show tangibly the production increment of stumping. Therefore, policy and development interventions should give emphasis to improvement of such institutional support system so as to achieve wider adoption of old coffee stumping technology.